Evaluasi Kualitas Pelayanan dan Dampaknya terhadap Kepuasan Pelanggan di Klinik Hewan - Winda Syafitri; Rizki Prafitri; Hari Dwi Utami (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze service quality in veterinary clinics and its impact on customer satisfaction. In the animal health industry, service quality is a key factor in ensuring customer comfort and pet welfare. This study reviews various studies that use quantitative, qualitative, or mixed methods approaches in measuring service aspects. Several dimensions of service quality analyzed include reliability, responsiveness, assurance, empathy, and tangibles. The results of the study indicate that empathy and responsiveness factors have the most significant influence on customer satisfaction, followed by reliability and assurance. Tangibles, such as clinic facilities and cleanliness, also play a role in shaping customer perceptions of the services provided. Although this study provides valuable insights, there are several limitations, such as limited coverage and lack of exploration of qualitative data. Therefore, further research is recommended to expand the geographical coverage and combine quantitative and qualitative methods to gain a deeper understanding. In addition, comparisons with human health services can provide new perspectives on customer expectations of veterinary clinics. The findings of this study are expected to be a reference for veterinary clinic owners and managers in improving service quality and customer satisfaction.